EVALUATION OF FOULING FACTOR ON HEAT EXCHANGER IN OIL GAS AND NATURAL OIL PROCESSING - Abdul Halim; Alif Gita Arumsari; Endang Ayu Sulistianingrum (Universitas Sahid, 2022)
Advances in science and technology of human civilization have encouraged industry in Indonesia to develop more and more advanced from simple technology to advanced technology. Chemical industrial technology is the use of engineering science that studies the processing of raw goods into more useful and economical goods which involve chemical reactions in the process. One of them is the technology to evaluate the Heat Echanger in the Chemical Industry, especially in the Oil and Gas Industry, Evaluation of the Heat Exchanger-05 to determine the fouling factor in the oil processing process so that if you know the fouling factor, the Heat Exchanger will be able to know what maintenance needs to be applied. equipment or not. Observing the process of making crude oil into products, diesel, residue and pertasol. From the calculation results, it is stated that the ratio of actual Rd and theoretical Rd is greater than the actual Rd than the theoretical Rd. The actual Rd is 0.02318648 The actual Rd value that can be obtained indicates that there is a buildup of fouling (crust) on the HE-05. The buildup of fouling can inhibit the rate of heat transfer between the residue and crude oil. In addition, this buildup of fouling can produce a hot slot area which can result in leaks in the heat exchanger. the heat given to the residue is 1919948,193 Btu/hour while the heat received by crude oil is 1682707,817 so it can be interpreted that not all the heat given by the residue is received by the crude oil. There is heat wasted by 14%. because it is necessary to add an insulator so that the HE performance is more efficient.